Karakter Kepemimpinan Katolik dalam Bingkai Teori 5 Level Kepemimpinan John C. Maxwell - Tri Sujarwadi (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
Effective leadership is crucial in every organization, including within the context of the Catholic Church. This study aims to analyze the character of Catholic leadership within the framework of John C. Maxwell's 5 Levels of Leadership Theory. The approach used in this research is descriptive-analytical, which seeks to explain how Maxwell's five levels of leadership Position, Permission, Production, People Development, and Pinnacle can be adapted to Catholic leadership. The study finds that each level of leadership has strong relevance in shaping better Catholic leadership character, with a focus on values such as service, integrity, and community development of faith. The implementation of this theory enables an increase in effectiveness in leading both the congregation and Catholic institutions as a whole.